Condition of invasiveness of Ulmus pumila L. in urboecosystem because of climatic changes (Ecological Bulletin of Kryvyi Rih District, 2019)
Climatic changes can affect heboundary distribution of natural and adventitious species’ plants. Fluctuations in air temperature, relative humidity and other factors can be a stimulus for the initiation and/or intensiﬁcation ofthe invasive nature of some adventive plant species, especially in regions with a high degree of anthropogenic transformation. The article presents the results of current state analysis and the prediction of invasiveness of adventitious species of Ulmus pumila L. (Chinese elm) in Primary Steppe because of climatic changes. The local population of U. pumila, which consists of young trees of different age, was discovered during a routine survey on the territory of a largeindustrial city Dnipro. The origin of seedy population has been determined, the number and denseness of undergrowth vegetation have been determined, the age and living conditions of the population have been studied. The statusof the invasiveness of identiﬁed local population U. pumila was substantiated. Mathematical models of the development of populations of Chinese elm’s seed origin in anthropogenically transformed ecotope (abandoned construction site)of Dnipro have been developed. Prediction on the preservation of tendency of growth of Chinese elm’s invasiveness in conditions of further changes in climate in the region has been done.
Keywords: Ulmus pumila; local population; invasiveness; climate change; modeling